Basic aspects of ketamine therapy for treatment-resistant depression - a review paper - Szafrańska, Weronika; Poborowska, Dominika; Gańko, Tomasz; Kahan, Weronika; Bąk, Emilia; Fordymacki, Jacek; Wojaczek, Marta; Polańska, Katarzyna; Najjar, Oliwia (Quality in Sport, 2024)
Introduction and purpose: Major depressive disorder (MDD) is the most common psychiatric illness, affecting millions of people worldwide. The first line of pharmacological treatment is usually monoamine reuptake inhibitors. Up to 60% of cases, may be drug-resistant patients, prompting researchers to research substances other than conventional. 1 The purpose of this article was to review recent studies on the use of ketamine in the treatment of drug-resistant depression and present their findings. Brief description of the state of knowledge: Ketamine has been a well-known drug used in anesthesiology and pain management for decades. Because of its multidirectional effects, researchers have become interested in its effects on psychiatric illnesses. Over the past decade or so, there has been a definite increase in research and articles on the use of ketamine in psychiatry. The study has resulted in FDA approval of esketamine for the treatment of treatment-resistant depression in adults in 2019. Material and method: This article is the result of searching keywords on databases such as Google Scholar and Pubmed and collecting scientific literature about depression and ketamine. Articles were preselected by title, number of citations, source, and publication date. Summary: Ketamine has the potential to be a treatment for drug-resistant depression. Its effectiveness varies with the form and dosage, with racemic and higher doses offering greater therapeutic benefits. Ketamine’s efficacy is on par with the electroconvulsive therapy. Its onset is faster than traditional antidepressants, significantly reducing suicide risk in a shorter time frame. While the precise mechanisms of its antidepressant effects are not fully understood, it is suggested that its impact on brain neuroplasticity may contribute to the rapid onset of action. Growing evidence supports ketamine’s effectiveness in treating TRD, highlighting the need for further research in this area.